Exposome and endocrine health - Buha Djordjević, Aleksandra (Archives of Pharmacy, 2022)
The term exposome describes every exposure from the environment to which an individual is subjected from conception to death. Rapidly increasing evidence has documented that exposure to endocrine-disrupting chemicals (EDCs), an important part of the exposome, substantially contributes to disease and dysfunction across the life span. To date, however, there have been few studies investigating simultaneous exposure to multiple EDCs in mixtures, although this scenario entails real-life exposures. This paper will present the “Decoding the role of exposome in endocrine health” – DecodExpo project funded by the Science Fund of the Republic of Serbia. The project aims to provide scientific evidence for the role of toxic metal(oid)s mixtures (As, Pb, Hg, Cd, Cr, and Ni) in the development of various endocrine disorders. The project consists of human biomonitoring (HBM), exposome-wide association, and animal studies. Namely, data on blood levels of toxic metal(oid)s in different cohort groups within the Serbian general population were collected (435 participants) and, by performing mathematical modelling, dose-response relationships were determined between certain toxic metals and hormone blood levels. The study protocol for the animal study was chosen based on the results of the HBM study, to address the main challenges in studies on EDCs (non-monotonic dose-response, long-term exposure to low doses, exposure to mixtures of EDCs, sex differences). Furthermore, various endpoints are tested to ensure better insight into molecular, biochemical, and structural changes in the endocrine system. The project revealed an important role of exposure to the investigated toxic metal(oid)s mixture in human endocrine health.